Legality of The Use of Lethal Autonomous Weapon System In The International Humanitarian Law Perspectives - Sholikah, Imroatus; Suryokumoro, Herman; Widagdo, Setyo (International Journal of Global Community, 2020)
Abstract International law in the world involves most international treaties as a step to limit the violations that occur. Where recently emerged new autonomous weapons. Where this weapon can choose and aim at targets without human intervention. The weapon is the Lethal Autonomous Weapon System, which, once activated, cannot isolate any of it to be attacked, whether combatants or non-combatants will even attack wherever they are regardless of the situation. This research is legal research that aims to examine how the legality of the Lethal Autonomous Weapon System is seen from International Humanitarian Law. This paper uses a normative legal research method with a qualitative approach to descriptive data analysis. The weapon’s mechanism is to defend when war is not to become an arena of unnecessary destruction and even cause casualties to civilians. There is a need for legal rules that limit or prohibit these weapons from operating. The Lethal Autonomous Weapon System is still very far away to fulfill the principles of International Humanitarian Law. It is unlikely that this weapon would be legal if there were no human intervention in its operation.